SAT0253 HLA-E as ligand for NKG2A/NKG2C in ankylosing spondylitis: Increased expression of HLA-E and prevalence of the inhibitory receptor. (23rd January 2014) - Cauli, A.; Dessole, G.; Porru, G.; Lai, S.; Camilli, G.; Vacca, A.; Piga, M.; Fiorillo, M.T.; Sorrentino, R.; Carcassi, C.; Mathieu, A.
Abstract : Background: Ankylosing Spondylitis (AS) is a complex chronic inflammatory disease strongly associated with the majority of HLA-B27 alleles. HLA-E are non classical MHC class I molecules that specifically interact with the natural killer receptors NKG2A (inhibitory) and NKG2C (activating), and have been recently proposed to be involved in AS pathogenesis. The two known HLA-E variants differ only at position 128, with either an arginine or a glycine, and this polymorphism has been demonstrated to be relevant in host immunity thus influencing the protection against HIV and HCV infection. Objectives: To analyze the expression of HLA-E and the CD94/NKG2 pair of receptors in HLA-B27 positive AS patients and healthy controls (HC) bearing the AS-associated (B*2705) and the non-AS-associated (B*2709) allele. Methods: The level of surface expression of HLA-E molecules on CD14 positive peripheral blood mononuclear cell was evaluated in 21 HLA-B*2705 patients with AS, 12 HLA-B*2705 healthy subjects (HC) and 12 HLA-B*2709 HC by using the monoclonal antibody MEM-E/08 (gift of Dr. Horejsi) in quantitative cytofluorimetric analysis and correlated with the Arg128/Gly128 genotype. Moreover, the HLA-E mRNA was also evaluated by real-time polymerase chain reaction (RT-PCR), GAPDH was used as reference. The percentage and density of expression of HLA-E ligands NKG2A (clone Z199; Beckman Coulter) and NKG2C (clone 134522; R&D) were also measured on CD3 - CD56 + NK cells. Values were expressed as median percentage of positive cells (interquartile range) and as cell surface antigen density in antibody binding capacity (ABC) units. The differences between AS patients and HCs were analyzed by one-way ANOVAs with Bonferroni post test and the two-tailed unpaired t-test with Welch's correction. Results: HLA-E expression on CD14 positive cells was significantly higher in AS patients (587.0 IQR 424-830) compared to B*2705 HC (389 IQR 251.3-440.5, p=0.0007) and B*2709 HC (294.5 IQR 209.5-422, p=0.0004). The amount of HLA-E molecules does not correlate with the polymorphism Arg128Gly as also confirmed by mRNA analysis on total PBMC (1.8 IQR 0.7-2.6 in AA bearing subjects, 1.8 IQR 1.0-2.7 in AG bearing subjects, GG not found). An increased number of NK cells expressing the inhibitory receptor NKG2A compared to the activating receptor NKG2C was found in AS patients (45.9% IQR 35.1-52.9 vs 8.5%, IQR 6.3-16.7; p<0.0001) as well as in either B*2705 HC (38.0% IQR 30.0-54.8 vs 8.0%, IQR 4.8-12.9; p<0.0001) or B*2709 HC (45.9% IQR 35.1-52.9 vs 7, 5% IQR 6.6-15.9; p<0.001). NKG2A also showed a higher cell surface density compared with the NKG2C receptor reaching statistical significance in AS patients (p=0.02) and B*2705 HCs (p=0.007). Conclusions: This study shows a higher expression of HLA-E molecules in AS patients compared to HC and an imbalance of NKG2A/NKG2C ratio with a larger expansion of NK cells expressing the inhibitory receptor which appears also more expressed on the cell surface. The higher surface level of HLA-E molecules in AS patients concurrently with a prevalent expression of NKG2A suggests that the crosstalk between these two molecules might play a role in AS pathogenesis accounting for the previously reported association between HLA-E and AS. Disclosure of Interest: None Declared